Dual-use research and research using enhanced pathogens in high-income countries: whose business? - Eyal, Nir M.; Leshabari, Melkizedeck; Sarker, Malabika (mSphere, 2024)
U.S. regulation of dual-use research of concern and of research with enhanced pathogens of pandemic potential may alter soon. Much has been written on the best form for that regulation to take. Less was written on a procedural question: whose voices should shape that regulation? This commentary addresses the latter, the procedural question, regarding the appropriate parties to the deliberations and decisions on this matter. It proposes to U.S. virologists that it would be in the interests of their discipline and only appropriate if that regulation were shaped by many voices from outside the discipline and from outside the United States.
Veröffentlicht: 13. Juni 2024
Gesehen am 26.11.2024